Exploring Gender Role in Co-Authorship Networks for Computing Books: A Case Study in DBLP - Kosovare Sahatqija; Arbana Kadriu (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Rovinj, Croatia, 12-14 September 2019, 2019)
Social network analysis and mining intend to explore for certain, previously unknown, and probably useful relational information from social and information networks. In our case, the research paper is about identifying collaborative networks between the authors (co-authors) of Computer Science books with the highlighted focus on the women computer scientist's community. Often the hardest part of collaborating is knowing whom you should be collaborating with. Hence, this study will tackle this issue and will identify, and present a visualization of the co-authors which have already collaborated and how often they have collaborated. In this way, we are going to distinguish the successful collaboration between co-authors, the trend of further collaboration between them and the participation of women on these collaborations. This paper is research which is based on detailed and intensive analysis of the different ways of identifying these kinds of connections through secondary material.
Keywords: C00; C30; 330; Gender role; co-authorship; DBLP; CS community